Avaliação e sustentabilidade dos Programas de Assentamentos Agrícolas no Estado do Ceará: um estudo de caso - Maia, Germano Silva (2012)
This study has the goal to evaluate, under many aspects, the agricultural settlement programs presently developed in the State of Ceará. This evaluation aims to detect the effectiveness of these public politics in the promotion of significant advancement. As an example, in the life quality of their beneficiaries. In order to achieve the aforesaid goal, it was made a research for primary data by the application of 170 questionnaires with beneficiary and non beneficiary rural producers, in the cities of Russas, Tabuleiro do Norte, Morada Nova and Ibicuitinga. It was made an extent revision of the literature, a detailed tabular study complemented by the application of statistic tests such as t Student, Chi-square, “U” de Mann–Whitney, and others. The analysis of political effectiveness was made by the construction of indexes with non matched data and the application of the Propensity Score Matching model, which is based in the matching of data. The study resulted in a rich characterization of the social economic profile of the interviewed and in conclusions of the analyses without matching very similar to the conclusions with data matching. These point to the non effectiveness of the politics in generating significant impacts in life quality, environmental development, politic institutional development, and others, to the beneficiaries when compared to those who are not contemplated by the politics.